Ethics of the Demand for Power of Prophet Sulaiman and Prophet Yusuf in Tafsir Fi Zhilal Al-Qur'an - Panda Jaya Halomoan; Siti Ardianti (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
Power in Islam is a divine mandate with ethical, spiritual, and social dimensions. However, the abuse of power in contemporary life demonstrates a shift in its meaning into an instrument of personal and group interests. Previous studies generally discussed the leadership of Prophet Sulaiman and Prophet Yusuf separately, resulting in a comparative examination of the ethical basis for their demands for power. This study aims to analyze the ethics of demands for power in the Qur'an through a comparison of the verses. QS. Ṣād [38]:35 and QS. Yūsuf [12]:55 based on the interpretation of Sayyid Quṭb in Tafsir Fi Zhilal Al-Qur'an. The research uses a qualitative approach with a descriptive-analytical method and a library research type. Primary data comes from Tafsir Fi Zhilal Al-Qur'an, while secondary data were obtained from relevant books and scientific articles. The data were analyzed using content analysis and comparative methods. The results of the study indicate two complementary ethical models of power demands: the transcendental-worship model in the story of the Prophet Sulaiman and the competence-benefit model in the story of the Prophet Yusuf. A comparison of the two yields four main principles: monotheistic orientation, moral integrity, competence supported by a track record, and commitment to the public good. Thus, a demand for power gains ethical legitimacy when based on devotion to God, accountable capabilities, and an orientation toward the public interest